2022
DOI: 10.1177/03128962211071128
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable sourcing and agility performance: The moderating effects of organizational ambidexterity and supply chain disruption

Abstract: Sustainable sourcing is an important sustainability practice yet its impact on the firm’s agility performance remains unexamined. Combining the extended resource-based view and contingency theory, this study hypothesizes that sustainable sourcing improves agility performance and this effect is enhanced by organizational ambidexterity and supply chain disruption. Using a sample of 790 manufacturing firms, the regression results show the positive performance effect of sustainable sourcing and the moderating role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…, 2021). Thus, supply chains should be maintained and modernised, taking new dimensions to ensure their sustainability in a changing environment by redesigning structures and re-planning long-term driven performance (Ivanov, 2020; Li et al. , 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021). Thus, supply chains should be maintained and modernised, taking new dimensions to ensure their sustainability in a changing environment by redesigning structures and re-planning long-term driven performance (Ivanov, 2020; Li et al. , 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, the sustainability of supply chains in the face of disruption depends on being agile, lean and resilient (Sarkis et al, 2020;Sharma et al, 2021). Thus, supply chains should be maintained and modernised, taking new dimensions to ensure their sustainability in a changing environment by redesigning structures and re-planning long-term driven performance (Ivanov, 2020;Li et al, 2022).…”
Section: Achieving Supply Chain Sustainabilitymentioning
confidence: 99%
“…Ref. [74] examined the relationship between visibility, exploration capability, and organizational performance in the context of SMEs in Sweden. The study found that both visibility and exploration capability positively influenced organizational performance, and that exploration capability partially mediated the relationship between visibility and performance.…”
Section: Relationship Between Visibility (Vs) Exploitation Capability...mentioning
confidence: 99%
“…There is a consensus in the literature that SSCM has become a competitive tool for firms to achieve continuous performance surpassing (Feng et al, 2020; Seuring and Müller, 2008; Yawar and Seuring, 2017; Zhu and Sarkis, 2004). SSCM, defined as the cooperating management of material, information, and capital flows among the supply chain members to achieve overall improvement in three dimensions of economic, environmental, and social practice (Seuring and Müller, 2008), can be implemented from the supplier management and customer cooperation (Feng et al, 2017; Li et al, 2022; Zhu et al, 2013). The former is triggered by the needs of avoiding related risks from regulation (Tong et al, 2018), supply chain disruption (Klassen and Vereecke, 2012), customer requirement (Choi et al, 2019; Zhu et al, 2017), and so on, to mitigate risks from supply chain on social and environmental dimensions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%